ANALISIS MANAJEMEN PELAYANAN TERPADU SATU PINTU DI PERGURUAN TINGGI - Hendri Sembiring; Hendri Indra; Ika Sartika (Jurnal Penelitian Samudra, 2025)
One-Stop Integrated Services (PTSP) in higher education institutions is an effort to improve the efficiency and quality of academic and administrative services. However, the implementation of PTSP management still faces various challenges, such as procedural inefficiencies, lack of supervision, and suboptimal service to users. This study aims to analyze the implementation of PTSP management based on the classic POAC management functions (Planning, Organizing, Actuating, and Supervision) and its impact on service quality in higher education institutions. The research method used is quantitative descriptive and verification, with a survey approach through questionnaires to 2 PTSP employees and 20 students as service users. The data analysis technique uses multiple linear regression to test the influence of management variables on service quality. The novelty of this study lies in the combination of the POAC model with the SERVQUAL dimension in the context of PTSP in higher education environments, which has not been widely studied before. Previous studies generally only discuss the implementation of PTSP in the government sector or have not emphasized the direct relationship between managerial functions and perceptions of service quality.